The Limits of Financial Imagination: Free Investors, Efficient Markets, and Crisis. Issue 1 (21st January 2014) - Ortiz, Horacio
ABSTRACT Fieldwork with a team of investment managers investing in credit derivatives in Paris in 2004 shows how the concepts of "investor" and "market efficiency" are central in the technicalities of their procedures, in diverse and contradictory ways. The employees refer to their moral and political contents, as they are articulated in liberal philosophy and in financial regulation, to make sense of their careers and of the social role of finance. "Crisis" is then defined as a deviation from market efficiency, itself expected to lead to an optimal allocation of credit. These concepts thus constitute the limited repertoire of the meaning of practical rules followed by employees for a remuneration, within a bureaucratic commercial network, in a setting very different from the utopias from which the concepts stem. Therefore, anthropologists must not use them as analytic tools; rather, such concepts should be understood as part of the object of study.